2011
DOI: 10.7748/nm2011.03.17.10.32.c8358
|View full text |Cite
|
Sign up to set email alerts
|

Patient participation in public elections: a literature review

Abstract: Healthcare organisations and nurse leaders have an important role in promoting patients' right to vote, through the development of policy guidelines, integrated networking and innovative practice. Patients' mental capacity to vote is usually assessed by nurses, who must therefore be aware of clients' voting rights and if the right resources are in place to help them do so. Patients' rights, as citizens, are recognised in law and in professional guidelines, but more needs to be done to protect their voting righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Healthcare interventions aimed at increasing voting rates have emerged within nursing, social work, and medicine. Regan, Hudson, and McRory conducted a literature review that looked at the role of nurses in ensuring patients' right to vote, issuing a call to action for nurses to help ensure this right through policy guidelines and increased support for patients [46]. Anderson and Dabelko-Schoeny argued that civic engagement can lead to better health in nursing home residents and called for social workers to develop and implement interventions that increase engagement [43].…”
Section: Healthcare Interventions Exist To Increase Voting and Democrmentioning
confidence: 99%
“…Healthcare interventions aimed at increasing voting rates have emerged within nursing, social work, and medicine. Regan, Hudson, and McRory conducted a literature review that looked at the role of nurses in ensuring patients' right to vote, issuing a call to action for nurses to help ensure this right through policy guidelines and increased support for patients [46]. Anderson and Dabelko-Schoeny argued that civic engagement can lead to better health in nursing home residents and called for social workers to develop and implement interventions that increase engagement [43].…”
Section: Healthcare Interventions Exist To Increase Voting and Democrmentioning
confidence: 99%
“…Although carers can lend support, the literature suggests that paid-carers have often been unaware or unsure of voting rights, with some staff fearful of influencing the voting choice of vulnerable groups and thus opening themselves to potential accusations of electoral fraud or vote rigging (Humphreys and Chiswick 1993;Smith and Humphreys 1997;Regan Hudson and McRory 2011). Other groups such as the elderly or Asian communities have been identified as potential targets for electoral fraud (Electoral Commission 2014), although this is an issue for all vulnerable groups, including people with intellectual disabilities (Antaki et al 2008;BBC News 2005;Rodgers, 1999;Humphreys and Chiswick 1993).…”
Section: Introductionmentioning
confidence: 99%
“…4,23 An under-representation of these voters may impact policy decisions pertaining to medical care and population health, and some studies have accordingly called for healthcare workers to address barriers to voting faced by patients. 2,7,8,[24][25][26][27] Importantly, several studies have indicated that enfranchising marginalized populations is associated with improved health outcomes, due to these voters disproportionately supporting policies focused on equity, including healthcare and education. 1,23,28 There are several ways that healthcare workers and institutions may act on this study's findings.…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies have analyzed the issue of voting while hospitalized, and earlier research has primarily focused on assessing competency for certain hospitalized populations, such as patients with dementia, and the under-representation of patients in the voting population. 8 , 21 , 22 A common finding from the literature is that ill patients may have different voting priorities than the general population, especially on matters related to healthcare. 4 , 23 An under-representation of these voters may impact policy decisions pertaining to medical care and population health, and some studies have accordingly called for healthcare workers to address barriers to voting faced by patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation